The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1080/03601239809373135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edifenphos and glyphosate on the immune response and protein biosynthesis of bolti fish (Tilapia nilotica)

Abstract: The effects of 1/1000 field recommended concentration of the organophosphorus compounds; edifenphos and glyphosate on the immune response and protein contents were investigated after different time intervals. The cell mediated immune response assessed by proliferative response of splenocytes to mitogens; phytohemagglutinin (PHA) and concanavalin A (Con A) for T cell and lipopolysaccharide (LPS) for B cell decreased significantly in tems of the level of stimulation index in the treated fish and reached maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…For example, El-Gendy et al (1998) found a decrease in the total protein content of serum that was concomitant with a change in the serum antibody titers in glyphosate-treated bolti fish. Kreutz et al (2011) also reported an altered phagocytic index, serum bacteria agglutination, and lysozyme activity in silver catfish following glyphosate-exposure.…”
Section: Introductionmentioning
confidence: 94%
“…For example, El-Gendy et al (1998) found a decrease in the total protein content of serum that was concomitant with a change in the serum antibody titers in glyphosate-treated bolti fish. Kreutz et al (2011) also reported an altered phagocytic index, serum bacteria agglutination, and lysozyme activity in silver catfish following glyphosate-exposure.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the data reported so far indicates that commercial formula of glyphosate causes a typical stress response on fish with a likely effect on immune response. Indeed, altered protein biosynthesis and immune function were observed in Tilapia (Tilapia nilotica) exposed to glyphosate [16].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of hinosan on fish toxicity was evident. El-Gendy et al (1998) studied the effects of hinosan on the immune response and protein biosynthesis. They declared that hinosan and glyphosate with 1/1000 concentration exhibit changes in the electrophoretic pattern of serum fish proteins.…”
Section: Discussionmentioning
confidence: 99%